Thoughts on the Visual Aspect of the Neoliberal Order and the Piquetero Movement in Argentina - Abal Medina, Paula (2010)
The Argentine piquetero movement of the 1990s, in which unemployed workers blockaded the roads to protest the neoliberal order, has been described as the emergence of a “visibility” that achieved political centrality. Visibility is a technology of power. The neoliberal order depends on the visual metaphor of “exclusion” or “obscurity” for the maintenance and reproduction of relations of domination. The subjects of this exclusion become living beings when they begin to struggle for visibility, exposing the relations of exploitation that characterize neoliberal capitalism. Such a struggle was launched by the piqueteros, and their blockades put an end to the darkness imposed upon them. In response, neoliberalism was forced to invent new ways of guaranteeing the reproduction of the social order, among them extortion (through the provision of temporary assistance) and repression (through the criminalization of protest), but the piqueteros’ efforts weakened the efficacy of these instruments of power. The subsequent reconfiguration of areas of social inclusion (first in the neighborhoods and then, especially since 2005, in the workplace) is largely the result of the emerging politicization that began with their struggles.